If the sum of the first terms of an arithmetic progression is equal to the sum of the first terms of the same arithmetic progression, where , find the sum for the first terms of the arithmetic progression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the first term and the common difference of the arithmetic progression be a 1 and d respectively. Then we have:
2 p ( 2 a 1 + ( p − 1 ) d ) 2 a 1 ( p − q ) ⟹ 2 a 1 = 2 q ( 2 a 1 + ( q − 1 ) d ) = ( q 2 − q − p 2 + p ) d = ( q − p ) ( q + p − 1 ) d = ( 1 − p − q ) d
Then the sum of the first p + q terms,
S p + q = 2 p + q ( 2 a 1 + ( p + q − 1 ) d ) = 2 p + q ( ( 1 − p − q ) d + ( p + q − 1 ) d ) = 0